The International Monetary System in the (Very) Long Run - Sussman, Nathan (IMF Working Papers; Working Paper ;, 2000)
This paper takes stock of the evolution of the international monetary system over the last thousand years. Several points stand out from the analysis. One is the reluctance of governments to embrace radical changes in international monetary relations. Another is the conflict between external and domestic objectives over the cycle, which has been a source of significant tension in the industrial core through much of this century, is now becoming a significant issue for developing countries. Finally, recent developments represent a return to the more market-driven international monetary system that characterized the better part of the preceeding millennium.